PENGEMBANGAN MEDIA INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 PADA MATERI NORMA DALAM KEHIDUPANKU KELAS V SEKOLAH DASAR - Putu Ayu Nita Andriani; L. Heny Nirmayani; I Ketut Ngurah Ardiawan (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This development research aims to develop interactive media based on Articulate Storyline 3, describe the design, analyze the level of validity, and analyze the level of practicality of interactive media based on Articulate Storyline 3. The model used in this study is ADDIE which consists of five stages, namely, Analyze, Design, Developmen, Implementation, and Evaluation. However, the development process in this study is limited to the Development stage. The research was conducted in Cluster V, Banjar District which includes five elementary schools, namely SDN 1 Sidetapa, SDN 2 Sidetapa, SDN 3 Sidetapa, SDN 1 Cempaga, and SDN 2 Cempaga. Validation of interactive media was carried out by three experts, namely media experts, material experts and language experts. Meanwhile, the practicality test was carried out by five grade V teachers and 50 grade V elementary school students. The results of the study showed that, 1) Interactive media based on Articulate Storyline 3 produces interactive learning activities with attractive designs for students equipped with pictures and learning videos. 2) The level of media validity is classified as very high with a media expert validation score of 0.95, material validity of 0.98, and language validity of 0.975. 3) The level of media practicality is included in the very practical category with a percentage of practicality from teachers of 98% and students of 97%. Based on the results of the validation and practicality test, interactive media based on Articulate Storyline 3 on the material Norma dalam Kehidupanku of Pancasila Education subjects for grade V elementary schools is declared feasible to be tested in the field.